Clinico-histopathological correlation in 3 patients with Lucio phenomenon: A serial case report - Yuniaswan, Anggun; Retnan, Diah Prabawati; Widasmara, Dhelya; Ekasari, Dhany Prafita; Sitaresmi, Adya (Journal of Pakistan Association of Dermatologists, 2023)
Lucio Phenomenon (LPh) is a reactional state usually observed in untreated or inadequately treated leprosy and is a life-threatening medical emergency. Several cases of LPh have been reported in Indonesia, which is an endemic country with highest burden of new case besides India and Brazil. Generally, histopathological findings in LPh reveal granulomatous and panniculitis reactions with vascular infiltration of acid fast bacilli. However, it is still debatable whether the main pathophysiology of necrosis is due to occlusive vasculopathy or immune complex-mediated process. In this study, we report clinical and histopathological descriptions of 3 patients with LPh. The first case was resulted with severe necrosis, mortality and massive bacilli infiltration with endothelial damage on histopathology examination. The second and third case presented less severe manifestation with multiple ulcers covered with hemorrhagic crust and mild necrosis. The histopathology examination showed minimal inflammation on the endothelial. This serial case report showed that histopathological examination might be useful as a prediction value on LPh since it can characterize the basic pathogenesis process. Lucio Phenomenon (LPh) is a reactionary stateÂ usually observed in untreated or inadequately treated leprosy and is a life-threatening medical emergency.